SYMBOLIC DEPICTIONS IN THE FITRAT STANZAS - Nazarova Shakhnoza Ibadullaevna (Scholar Express Journals, 2021)
The article analyzes the symbolic features of the images used in Fitrat's poetry, in particular, in the series "Woe to the country", their poetic function and worldview aspects
Keywords: stanza; symbolic fantasy image; symbolic image of a sad mother; portrait